Tools for Occupational Diseases Control in the Artisan Figures of Marzipan - Álvarez, Ana (2022)
A worker in an eight-hour workday is exposed to muscle aches or numbness in the legs and fatigue. Matrices were made for the identification and evaluation of physical risks to the population of artisans of marzipan figures in the parish of Calderon in Quito Ecuador, ergonomic evaluation methods were also applied such as: The RULA, Check list OCRA and the NIOSH equation. Five stages that make up the production process were identified: Preparation of the dough, kneading, shaping and finishing, varnishing, and drying, of all these stages the drying process is the most time consuming, the shaping and finishing stage is the one that more work and details requires, the kneading is in which a standing posture is maintained by the craftsman and with repetitive movements. It is necessary to implement a production system with well-defined phases, it is necessary to redesign the jobs that present a high level of ergonomic and physical risk, once the improvements proposed in the project have been applied, it is essential to maintain constant training with the artisans.